Evaluation of The Arabic Text Reading Skills Model Based On The Integrated Dini Curriculum Inquiry Activity: A Fuzzy Delphi Approach - Zulkifli Din Mohamed Nasirudin; Harun Baharudin; Nik Mohd Rahimi Nik Yusoff; Nabihah Yusof (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study was conducted to evaluate the applicability of an Arabic text reading skills model based on the Integrated Dini Curriculum inquiry activities. This study uses a Design Development Research (DDR) founded by Richey and Klein (2007). The development process of this model is based on Constructivism Theory (Vygotsky, 1978) and a combination of three models, namely the Inquiry Model (Alberta Learning, 2004), the Cognitive Model of Reading Comprehension (McKenna Stahl, 2015), and the Interactive Reading Model (Rumelhart, 1997). This study involves three phases: analysis, design and development, and evaluation, but this article focuses on evaluation. The purpose study is to evaluate the Arabic text reading skills model based on inquiry activities using the Fuzzy Delphi approach involving eleven experts. The findings indicate a high consensus from the expert panel. In conclusion, this study produces a model of Arabic text reading skills based on inquiry activities to produce students who master the skills of reading Arabic text well. The study can also be used as a guide to help teachers plan more effective teaching and learning activities. The researcher suggested that the model of Arabic text reading skills based on this inquiry activity be detailed as modules in the future.